PENGEMBANGAN STRATEGI PEMASARAN PADA BISNIS USAHA COFFEE XYZ MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS (AHP) - Raihan Fadhilah Purba, Muhammad; Chirzun, Ahmad; Parwati, Niken; Tri Purwandari, Aprilia (LPPM Universitas Bina Bangsa, 2024)
A cafe called Cafe XYZ is located at Pasar Minggu. Apart from heavy and light food, Cafe XYZ serves a selection of drinks, specializing in coffee drinks, cereal, and ice cream. Even though this cafe has been around for seven years, there are still obstacles that must be resolved so that sales can increase. However, Cafe XYZ's business is still experiencing problems. Among them are products that are not updated on social media, product promotions that are incomplete, and according to the owner, sales targets are lacking, sales strategies are lacking, and market segmentation is still too narrow. Therefore, to achieve a good strategy, strategy development is needed. Based on research that has been carried out, the Cartesian diagram shows that in quadrant I growth and development (grow and build) use the SO strategy. By using the Analytical Hierarchy Process (AHP), the results showed that the best strategy selection was to use the SO strategy by offering customization for customers to customize their coffee.